Anthropometric factors affecting buoyancy in the African - Ghesquiere, J. L.; Karvonen, M. J. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
In recent years, Africans have excelled in a great variety of sports. Even long distance running, for which the body build and the physiological characteristics of the African were previously considerd as less well suited, has at the recent Olympic games become a1most a monopoly of Africans. There is, however, a notable exception ; swimming. The absence of African swimmers, or swimmers of African origin, from the world elite is indeed conspicuous. In swimming, work has to be done against gravity in order to keep the swimmer on the surface and to overcome the resistance of water for forward movement. A relatively light body floats well, whereas a human body with higher density requires a greater proportion of the total energy being spent against gravity.